Human Resources Information System Analysis - Krulíková, Dagmar (2008)
One of the biggest and prolonged capital assets of society is investment in staff. If they are managed in the right way, these investments can be the source of innovation and growth, competitive advantage and previsions of leading position in the market. Viz.[7] This Diploma thesis is aimed on the analyses of the human resources management, structure and demands on the personal information system, which solves this area as a whole. Described systems and solutions are generalization of the author's theoretical and practical experiences with particular human resources information system. There are defined the demands on common concept of HR IS. In this diploma thesis you can find the description